The role of human capital in enhancing organizational competitiveness: A literature review - Rudihartati, Leny; Dwiono, Sugeng (Junal Ilmu Manajemen, 2025)
This study seeks to investigate the impact of human capital on improving organizational competitiveness via innovation, efficiency, and organizational learning. In the realm of globalization and intensifying competition, human capital is recognized as a strategic asset that can enhance organizational performance. This study used a systematic literature review (SLR) methodology to identify critical components of human capital, including employee competencies and organizational learning, that substantially enhance creativity and operational efficiency. The research findings indicate that investing in staff competency development enhances productivity and fosters an environment conducive to creativity. Furthermore, organizational learning is essential for improving adaptability to market and technology shifts. This research finds various impediments, including insufficient investment in personnel development and difficulties in adapting to technological advances. This research recommends investing in training, fostering a learning culture, and establishing a transparent performance management system. This research underscores the vital importance of human capital in establishing sustainable competitiveness for firms in the current competitive landscape.